Upaya Pencegahan Terhadap Anak Korban Kekerasan Verbal (Catcalling) Pada Lingkungan Pendidikan - Maspaitella, Roshanty Putri; Sopacua, Margie Gladies; Saimima, Judy Maria (Faculty of Law Universitas Pattimura, 2025)
Violence that occurs in society against women, one of which is verbal sexual harassment, such as catcalling, is a form of behavior that can deprive a person of their human rights, especially the right to live a peaceful life, feel safe in their activities, build a life in peace, and feel physical and mental happiness in the community. Cases of verbal violence often occur in educational settings such as what happened in Ambon on April 11, 2024 by a student of SMA Negeri 5 Ambon with the initials AFM and the same case on April 2, 2025 experienced by a female student with the initials SW, where they committed verbal violence with sentences that harassed the body shape of their schoolmates. The research method used is normative research, a statutory approach, primary and secondary legal materials and material collection procedures using literature studies. Prevention efforts for child victims of verbal violence (catcalling) in the educational environment are 1) Having the ability or courage to stare at the perpetrator and leave immediately, if you have to pass a group of people who commit verbal violence (catcalling) during the day, the victim can stop for a moment and look at the perpetrator firmly: 2) Avoid wearing flashy jewelry, when walking alone, especially in a quiet place or a group of strangers, it is advisable not to wear flashy or excessive jewelry and 3) Be confident and try to think positively, that we can prevent this form of verbal violence (catcalling) by educating or socializing the law to children in the educational environment.